Young employees' perceptions about employability skills for e-commerce - Ildikó Kovács; Éva Réka Keresztes (Economies, 2022)
With the digital transformation of businesses, digital marketing has been a prominent feature of organizations in the 21st century. Changing consumer behavior has also created a need for versatile hard and soft skills for marketing professionals. Inspired by the ongoing disruption to businesses across the world, this research focuses on employability skills in the field of e-commerce. A systematic review of the managerial research literature on digital marketing and e-commerce competencies has revealed a research gap regarding the investigation of the perceived importance of employability skills. The aim of this paper is to find out how important these skills are for future and current employees. The novelty of this study is the comparison between perceptions related to nonworking versus working young employees based on five key skill categories across 30 soft and hard skills. The study is quantitative in nature: a self-administered computer-assisted personal interviewing (CAPI) method is used for data collection. The findings reveal that the examined skills are perceived as important from the employee point of view. In addition to exploring the perceived relevance of the employability skills categories, the study identifies differences among the skills that young workers consider important in terms of their work experience. The research results reveal significant differences by work segments in relation to soft skills, such as teamwork, stress resilience, planning, organization and time management, precision, and attention to detail.
Keywords: 330; e-commerce; employability skills; skills perceptions; young employees